The Peterson Case and its Impact on the Rules in Ben Nevis - Coleman, James (Victoria University of Wellington Law Review, 2022)
This article revisits and builds upon Professor Prebble’s 2006 book chapter "The Peterson Case and its Impact on the Rules in BNZ Investments Ltd and Cecil Bros", considering the ways in which the Peterson case has influenced the leading 2009 New Zealand tax avoidance case of Ben Nevis. The article argues that Ben Nevis actually follows Peterson in two ways. First, it adopts the analysis of both the majority and the minority judgments in Peterson to the effect that the general anti-avoidance provision only applies when the purpose of the particular provision has been thwarted. Secondly, it uses the minority’s less judicial approach in considering whether the purpose of the specific provision has been complied with or not. The minority allowed a greater sweep of material to be relevant and inform that decision than the majority did. The majority looked only to the contractual rights and obligations created.